Analysis of the Implementation of the First Level Outpatient Referral for Bpjs Kesehatan Participants at the Medan City Exemplary Health Center in 2023 - Lubis, Anisah; Asriwati, Asriwati; Subaedah, Sitti (PROMOTOR, 2025)
The Social Security Administration Agency or BPJS Kesehatan recorded a total of 267.31 million participants as of December 31, 2023. If they need follow-up services by a specialist doctor, BPJS Kesehatan participants can be referred to second-level health facilities or secondary-level health facilities. The causes of the high number of referrals at the Teladan Health Center are due to: inadequate availability of doctors, delays in the availability of drugs and frequent vacancies in drug stocks, lack of availability of medical facilities and medical equipment and the implementation of the FKTP function as a gatekeeper does not follow the established rules. This research is a qualitative descriptive research, which is a research method that is carried out with the main purpose of making an overview or description of a situation objectively, with a semi-structured interview method, which is a type of interview that includes the category of in-depth interviews recorded using a tape recorder where in its implementation it is freer when compared to structured interviews. The results of the study obtained from this study are that there are still many referrals on their own request because patients do not trust the health center, resulting in a high number of referrals. The number of health workers at the Teladan Health Center has met the standards, but neurologists and cardiologists are needed because many of the patients referred have internal diseases. Medicines, medical devices, medical device facilities and infrastructure facilities at the Teladan Health Center are incomplete and there is a lack of public knowledge about the gatekeeper concept so that there are frequent APS referrals. It is hoped that the Exemplary Health Center to the Head of the Health Center will propose the addition of Specialist Doctors to the Medan City Health Office, re-evaluate drug planning, provide socialization to the public about JKN, especially the tiered referral system and about the gatekeeper concept. The Medan City Health Office is also expected to collaborate with health centers in completing medical equipment and medicine facilities.